2021
DOI: 10.3390/ijms22062993
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Gut Microbiota in the Gut–Brain Axis in Obesity: Mechanisms and Future Implications

Abstract: Interaction between the gut and the brain is essential for energy homeostasis. In obesity, this homeostasis is disrupted, leading to a positive energy balance and weight gain. Obesity is a global epidemic that affects individual health and strains the socioeconomic system. Microbial dysbiosis has long been reported in obesity and obesity-related disorders. More recent literature has focused on the interaction of the gut microbiota and its metabolites on human brain and behavior. Developing strategies that targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
10

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 199 publications
0
26
0
10
Order By: Relevance
“…obesity is closely related to the intestinal flora. 17,51,52 Finally, unlike their study, none of our patients had recently taken medication for narcolepsy. According to some estimation, more than a quarter of 1000 drugs we used, most of which were not antibiotics, are likely to affect gut flora.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…obesity is closely related to the intestinal flora. 17,51,52 Finally, unlike their study, none of our patients had recently taken medication for narcolepsy. According to some estimation, more than a quarter of 1000 drugs we used, most of which were not antibiotics, are likely to affect gut flora.…”
mentioning
confidence: 75%
“…Since most patients with NT1 are accompanied by obesity, which is closely related to intestinal bacteria, 17,51,52 we examined the relationship between obesity and intestinal bacteria of NT1, and BMI was not taken as a covariable in the present study. Partial correlation analysis was conducted between the different flora of NT1 and abnormal clinical features.…”
Section: Correlation Between Clinical Features Of Nt1 and Gut Microbiotamentioning
confidence: 99%
“…Bacteria and their products are vital contributors to impairment and permeability of the gut barrier, resulting in an increased influx of bacteria, endotoxin, bacterial DNA, and metabolites into the host circulation. Recent reviews show that microbial dysbiosis and impaired barrier function are associated with gastrointestinal disease [113][114][115], neurodegenerative disease [116][117][118][119], autoimmune disease [120][121][122][123][124][125], and an impaired metabolic status in the host manifested by obesity, insulin resistance and cardiovascular complications [126][127][128][129][130][131][132][133][134][135]. In several animal models [63,64,107,136,137], exposure to PQQ increases mRNA expression levels of tight junction proteins and improves jejunal barrier function, suggesting PQQ may act through the gut to affect tissues in the periphery.…”
Section: Intestinal Barrier Functions and The Microbiomementioning
confidence: 99%
“…Obesity is associated with altered gut microbial composition in mice and humans, and the trait is transmissible as colonization of germ-free mice with microbiota from obese mice led to a significant increase in body fat compared to colonization with microbiota from lean mice ( Turnbaugh et al, 2006 ), suggesting that gut microbiome is part of the host metabolic system actively regulating energy balance ( Bäckhed et al, 2004 ). It has also been suggested that microbiome plays a crucial role in the communication between the gut and brain (microbiota-gut-brain axis), which is essential for the regulation of energy homeostasis ( Romaní-Pérez et al, 2021 ; van Son et al, 2021 ) as well as the development and functions of the nervous system ( Chen et al, 2021 ; Gwak and Chang, 2021 ). Consequently, altered gut microbiota (dysbiosis) has been implicated in a number of chronic inflammatory diseases, such as diabetes ( Zawada et al, 2020 ; Rodriguez and Delzenne, 2021 ) and neurodegenerative disorders, including AD ( Jiang et al, 2017 ; Chen et al, 2021 ; Leblhuber et al, 2021 ; Romanenko et al, 2021 ).…”
Section: Insulin and Leptin Mediating The Link Between Infection And Neurodegenerative Disordersmentioning
confidence: 99%